Microorganisms and Antibiotic Profile of the Subpreputial Space in Uncircumcised Boys - Demir, Selamettin; Ragbetli, Cennet; Kankilic, Nazim Abdulkadir; Yildiz, Abdullah; Bitkin, Alper (Urology Journal, 2020)
Purpose: This study investigates the frequency of isolated microorganisms and the antimicrobial resistant pattern of inner foreskin and smegma in prepubertal children. Materials and Methods: This comparative cross-sectional study was conducted between March and November 2019, where 132 prepubertal boys, who were scheduled to receive religious circumcisions at our outpatient clinic, were examined. The patients were divided into the following groups based on the presence of smegma in their subpreputial space: Group I (with smegma, n=58) and Group II (without smegma, n=74). Sterile stuart transport swabs (Advanced Diagnostic Research, Mediko Kimya, Turkey) were taken from the smegma or the subpreputial space (glans surface and inner foreskin) using aseptic techniques and then the swab samples were immediately transported by sterile stuart transportation for microscopy, culture identification, and antibiographic resistance testing by conventional test methods and automated systems (VITEK II, Biomerieux, France) to the Microbiological Laboratory of our hospital. Results: 48 bacteria isolated from 39 boys in Group I comprised 28 gram-positive species (58.3%) and 20 gram-negative species (41.7%). The most commonly isolated gram-negative bacterium was Proteus mirabilis (45%) while most positive was Staphylococcus hominis (42.9%). In Group II, 68 boys had 103 bacterial isolates in the glans comprising 81 gram-positive species (78.6%) and 22 gram-negative species (21.4%). The most commonly isolated gram-negative bacterium was Proteus mirabilis (42.9%) while the most positive were Enterococcus faecalis (40.7%) and S. hominis (42.9%) Conclusion: The subpreputial space of uncircumcised boys is colonized by various types of uropathogens resistant to multidrug drugs. Smegma does not pose additional risks to microbiological colonization in children.